A Role for WNT/β-Catenin Signaling in the Neural Mechanisms of Behavior - Maguschak, Kimberly A. (2012)
Wnt signaling pathways play a role in a variety of cellular processes including development, cell proliferation, cell fate, and motility. The Wnt/β-catenin pathway is among the most studied of the Wnt pathways and is highly conserved throughout evolution. Recent in vitro and slice physiology experiments have shown that this pathway also functions in synaptic transmission and activity-dependent synaptic plasticity. Since it has now been shown that many components of this signaling pathway are found in the adult brain, Wnt/β-catenin signaling may be important for maintaining and protecting neural connections throughout the lifespan. Here we summarize the role of Wnt/β-catenin signaling in the postnatal brain and discuss recent studies suggesting that deregulated Wnt signaling can result in altered behavior and cognitive disorders.